The involvement of musculoskeletal system and its influence on postural stability in children and young adults with cystic fibrosis - Ozge Kenis-Coskun; Evrim Karadag-Saygi; Yeliz Bahar-Ozdemir; Yasemin Gokdemir; Bulent Karadag; Onder Kayhan (BMC, 2017)
Abstract Background Cystic fibrosis (CF) affects the musculoskeletal system via a multifactorial pathway that includes vitamin D deficiency and involvement of respiratory muscles such as intercostals due to recurrent upper and lower respiratory tract infections. Eventual result is the deterioration of musculoskeletal health and posture in CF patients. Postural stability is directly affected by posture and can be compromised in every musculoskeletal problem. The aim of this study is to evaluate musculoskeletal system and postural stability in patients with CF. Methods Patients with CF over six years of age and age and sex-matched control groups were included in the study. Cobb angle and thoracic kyphosis angles were measured on the spine radiographs. Both patients and control group were examined with pediatric gait, arms, legs and spine scale (pGALS). They also were evaluated with a NeuroCom Balance Master for their postural stability. Results Fifty-one patients with CF and 94 healthy controls participated in the study. In results of the pGALS examination, CF group had significantly more pathological findings than the control group in lower extremity appearance and movement (p = 0.006 and p = 0.01) and spine appearance and movement (p = 0.001 and p = 0.022) domains. The tandem walking speed was significantly higher in controls with a mean of 24.45 ± 7.79 while it was 20.47 ± 6.95 in the CF group (p = 0.03). Various limits of stability parameters also showed significant differences. Medium correlations were found between musculoskeletal examination and postural stability parameters. Conclusion In patients with CF, a systematic but simple musculoskeletal examination can detect pathologies, which are more frequent than the normal population. These pathologies show a medium correlation with the involvement of postural stability.